Historiografia de espécies da família urticaceae coletadas no Brasil e depositadas nos herbários de Kew, New York e Paris - Corrado, Amanda Roberta [UNESP] (2014)
Exsiccates forms a mixed document, in which the fixed plant represents the biological evidence and the registers of the label, the textual evidence. The biological evidence of the exsiccata is the basis for the study of the taxonomy and systematic which normally uses the observation and comparison of the fixed plant for the review and updating of the nomenclature. As a documental source, the series of exsiccates have been studied in this work with focus on the textual evidence. Through the revisiting, recovery and systematization of registers, information was gathered on: (1) common name of the plants; (2) usage, (3) perception on the relation human-natural and (4) historical aspects of the collection analyzed. The study has approached the series of exsiccates of the family deposited in three foreign institutions: (1) Royal Botanic Gardens (K), Kew, England; (2) Muséum National d'Histoire Naturelle (P), Paris, France, which have participated in the Project REFLORA; (3) New York Botanical Garden (NY), United States, together with printed sources and manuscripts. A total of 2644 exsiccates, have been analyzed, 707 from K, 542 from P and 1395 from NY, and eight historical works. With the analysis of the data, 50 species of the family Urticaceae presented registers of popular names, of which the genre Cecropia outstands. Thirty-five exsicatas presented indication of use of the species collected categorized in (1) medicinal; (2) human food; (3) animal food; (4) fiber and (5) energy. The species with register of use were: Boehmeria nivea (L.) Gaudich., Cecropia concolor Willd., C. obtusa Trécul, C. pachystachya Trécul, Laportea aestuans (L.) Chew, Pourouma cecropiifolia Mart., P. cucura Standl. & Cuatrec., P. guianensis Aubl., P. minor Benoist, Urera baccifera (L.) Gaudich. ex Wedd., U. caracasana (Jacq.) Gaudich. ex Griseb., U. punu Wedd. The description of the historical aspects of formation of the ...